The effect of alkali earth metals on CuO/Al₂O₃ oxygen carrier in syngas chemical looping combustion process - Chang, Chia Chyi (Nanyang Technological University, 2022)
Chemical looping combustion (CLC) is a promising technology which could serve as a possible replacement for combustion of fossil fuel and incineration of municipal solid waste (MSW). This process involves the use of oxygen carriers to transfer oxygen from the air reactor to the fuel reactor without direct contact between the two reactors. CuO is one of the most commonly used metal oxide for oxygen carriers. However, due to the low melting points of CuO, it brings about problems of sintering and agglomeration which could defluidize the reactor. Over the years, researchers have been experimenting with different metal oxides and/or adding supports such as Al2O3 to the active phase metal oxide, in order to improve the performance of the oxygen carrier. Presently, little research has been done on the influence of sorbents in the performance of oxygen carriers for CLC.